Poklicni feminativi v slovarskih virih in v razpisih za delovna mesta - Markežič, Tjaša; Stramljič Breznik, Irena (Slavia Centralis, 2020)
FEMINATIVES DENOTING PROFESSIONS IN DICTIONARY RESOURCES AND JOB ADVERTISEMENTSThe article brings an overview of feminatives used for professions that are set out in the Standard Classification of Professions. The occurrence of feminatives has been examined in various Slovenian language sources. As expected, more professional feminatives are present in contemporary language sources than in older ones. According to the research, usage of just feminine denominations for professions is in the minority, but the occurrence of masculine forms is also conditioned by the chronological order of the language source publication. Consequently, at least from a linguistic point of view, gender equality in the labour market and labour division is aimed at. The implementation of the issue was verified in job advertisements published on the website of the Employment Service of the Republic of Slovenia. However, the results show the indication of only a male gender designation for the profession predominates; the equivalent use of female and male names do not reach even two per cent.
Keywords: word formation; feminatives; professions; job advertisements